Monoclonal Antibodies Targeting IL-5 or IL-5Rα in Eosinophilic Chronic Obstructive Pulmonary Disease: A Systematic Review and Meta-Analysis - Zhang, Chuchu; Wang, Yalei; Zhang, Meng; Su, Xiaojie; Lei, Ting; Yu, Haichuan; Liu, Jian (Frontiers in Pharmacology, 2021)
Background: Although the predominant airway inflammation in chronic obstructive pulmonary disease (COPD) is neutrophilic, approximately 20–40% of COPD patients present with eosinophilic airway inflammation. Compared with non-eosinophilic COPD patients, eosinophilic COPD patients are characterized by a greater number of total exacerbations and higher hospitalization rates. Furthermore, anti-interleukin-5 (IL-5) therapy, consisting of monoclonal antibodies (mAbs) targeting IL-5 or IL-5 receptor α (IL-5Rα), has been proven to be effective in severe eosinophilic asthma. This meta-analysis aimed to determine the efficacy and safety of anti-IL-5 therapy in eosinophilic COPD. Methods: We searched the PubMed, Web of Science, Embase, and Cochrane Library databases from inception to August 2020 (updated in June 2021) to identify studies comparing anti-IL-5 therapy (including mepolizumab, benralizumab, and reslizumab) with placebo in eosinophilic COPD patients. Results: Anti-IL-5 therapy was associated with a decrease in acute exacerbation rate (RR 0.89; 95% CI 0.84 to 0.95, I2 = 0%) and the severe adverse events (RR 0.90; 95% CI 0.84 to 0.97, I2 = 0%). However, no significant improvement was observed in pre-bronchodilator forced expiratory volume in 1 s (FEV1) (WMD 0.01; 95% CI −0.01 to 0.03, I2 = 25.9%), SGRQ score (WMD −1.17; 95% CI −2.05 to −0.29, I2 = 0%), and hospital admission rate (RR 0.91; 95% CI 0.78 to 1.07, I2 = 20.8%). Conclusion: Anti-IL-5 therapy significantly reduced the annual acute exacerbation rate and severe adverse events in eosinophilic COPD patients. However, it did not improve lung function, quality of life, and hospitalization rate.